Performance evaluation of novel fluorescent-based lateral flow immunoassay (LFIA) for rapid detection and quantification of total anti-SARS-CoV-2 S-RBD binding antibodies in infected individuals - Farah M. Shurrab (16324961) (2022)
Background A vast majority of the commercially available lateral flow immunoassay (LFIA) is used to detect SARS-CoV-2 antibodies qualitatively. Recently, a novel fluorescence-based lateral flow immunoassay (LFIA) test was developed for quantitative measurement of the total binding antibody units (BAUs) (BAU/mL) against SARS-CoV-2 spike protein receptor-binding domain (S-RBD). Aim This study aimed to evaluate the performance of the fluorescence LFIA FinecareTM 2019-nCoV S-RBD test along with its reader (Model No.: FS-113). Methods Plasma from 150 reverse trancriptase–PCR (RT-PCR)-confirmed positive individuals and 100 prepandemic samples were tested by FincareTM to access sensitivity and specificity. For qualitative and quantitative validation of the FinCareTM measurements, BAU/mL results of FinCareTM were compared with results of 2 reference assays: the surrogate virus-neutralizing test (sVNT, GenScript Biotech, USA) and the VIDAS®3 automated assay (BioMérieux, France). Results FinecareTM showed 92% sensitivity and 100% specificity compared with PCR. Cohen's Kappa statistic denoted moderate and excellent agreement with sVNT and VIDAS®3, with values being 0.557 (95% CI: 0.32–0.78) and 0.731 (95% CI: 0.51–0.95), respectively. A strong correlation was observed between FinecareTM/sVNT (r = 0.7, p < 0.0001) and FinecareTM/VIDAS®3 (r = 0.8, p < 0.0001). Conclusion FinecareTM is a reliable assay and can be used as a surrogate to assess binding and neutralizing antibody response after infection or vaccination, particularly in none or small laboratory settings. Other Information Published in: International Journal of Infectious Diseases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijid.2022.02.052